PL.53 A Retrospective Analysis on Complications and Management of Macrosomic Babies. (26th April 2013) - Pillai, RN; Davidson, T; Singhal, T; Matiluko, A
Abstract : Introduction: Considerable disparity has been noticed in macrosomic deliveries due to lack of recognised guideline in the management of macrosomia. In this study, we determined risk factors predicting macrosomia and associated complications. We analysed variations in management of macrosomia in a large teaching hospital. Method: This study was done by retrospective analysis of case notes of 45 women who delivered macrosomic babies from January 2010 to June 2010 in university hospitals of Leicester NHS trust. Results: Incidence of macrosomia was highest in the age group 30–40 years (46%). About 71% of babies with macrosomia in our analysis occurred in women with BMI < 30. Eighty % of macrosomic babies were born to non-diabetic mothers. Prior incidence of macrosomia occured in 17.9% of multiparous women in our sample. Our analysis highlighted the variations in management of macrosomia, typically in mode of delivery (Table 1 ). Conclusion: In our analysis, we concluded that it is difficult to anticipate macrosomia based on risk factors. Also, there is a high incidence of complications associated with macrosomic deliveries. This highlights need for regular obstetric emergency 'skills and drills'. There is a need for standardised guidelines on management of macrosomia.